REVIEW ASSESSMENT OF BIODIVERSITY LOSS OF SUNDARBAN FOREST: HIGHLIGHTS ON CAUSES AND IMPACTS - Shohel Khan, Md.; Abdullah, Shahriar; Abdus Salam, Mohammed; Rani Mandal, Tanwee; Rajib Hossain, Md. (Association of Indonesian Forestry and Environment Researchers and Technicians, 2021)
Sundarban, the world biggest mangrove forest, was announced as a World Heritage in 1997 and Ramsar Site in 2007. It's 62% lies in Bangladesh (Khulna, Bagerhat, Satkhira, Pirojpur, and Barguna Regions) and 38% in India, which become a vanguard for coastal communities. This ecosystem's floral and faunal structure incorporates 334 floral, 300 birds, 120 fish, 35 reptiles, and 32 mammals species. It contributes 41% of the total forest income of Bangladesh. This paper is intended to recognize the significant reasons for biodiversity calamity and its related effects on lives and degradation of the environment. A total of 105 published articles and reports were identified by searching four keywords: degradation, biodiversity, Sundarban, and Bangladesh. By considering the scope, 28 articles and 17 reports were incorporated to satisfy the objectives. The study revealed that the prominent causes of biodiversity loss of Sundarban might be due to intensified shrimp cultivation, increased dependency on forest and illicit felling, changing land use pattern, oil spillage, and pollution, forest fire, improper management practices, plant diseases, tourism activities, upstream withdrawal of river water, salinity intrusion, climate change, and some natural causes. The impacts were the loss of diversity of floral and faunal species subjected to regionally extinct, critically endangered, endangered, vulnerable, near threatened, and least concern condition. Finally, the study recommended the formulation of a special mangrove forest policy and proper management practices of Sundarban with several environmental protection strategies that should be adopted to conserve this unique ecosystem